1979
DOI: 10.3109/13682827909011361
|View full text |Cite
|
Sign up to set email alerts
|

The Long Term Use of an Automatically Triggered Auditory Feedback Masking Device in the Treatment of Stammering

Abstract: Summary Portable and Clinical Bench models of an automatically triggered auditory feedback masking device, the “Edinburgh Masker”, and their usage are described. The device was found to be effective in abolishing or greatly reducing stammering in 89% of 195 cases. The effectiveness of the portable device has continued in the majority of users during periods of observation of up to three years. In a follow‐up study of 67 subjects with six months or more experience of the Masker, 82 % considered it to be of “con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
11
0

Year Published

1986
1986
2020
2020

Publication Types

Select...
5
3
2

Relationship

0
10

Authors

Journals

citations
Cited by 38 publications
(12 citation statements)
references
References 12 publications
1
11
0
Order By: Relevance
“…Earlier research has demonstrated that a wearable, albeit not ear level device, delivering AAF maintained long-term stuttering inhibition. 30 The "Edinburgh masker" diminished stuttering in 89% of 195 persons who stutter. Six months to three years latter, of 62 who were followed, 82% were found to have maintained reduced stuttering.…”
Section: Discussionmentioning
confidence: 99%
“…Earlier research has demonstrated that a wearable, albeit not ear level device, delivering AAF maintained long-term stuttering inhibition. 30 The "Edinburgh masker" diminished stuttering in 89% of 195 persons who stutter. Six months to three years latter, of 62 who were followed, 82% were found to have maintained reduced stuttering.…”
Section: Discussionmentioning
confidence: 99%
“…The effect of masking on stuttering has been well documented and a portable device delivering masking was subsequently developed for use in everyday speaking situations (Block, Ingham, & Bench, 1996;Gruber, 1971;Dewar & Dewar, 1979). However, interest in masking as a tool to help control stuttering waned in the eighties as a result of studies which found that DAF and FAF were more effective in reducing stuttering than masking (Howell, El-Yaniv, & Powell, 1987;Kalinowski, Armson, Roland-Mieszkowski, Stuart, & Gracco, 1993).…”
Section: Introductionmentioning
confidence: 97%
“…Each of these auditory alterations has been found to immediately reduce stuttering frequency, although DAF and FAF have proven to be more effective that MAF (Howell et al, 1987;Kalinowski et al, 1993). With empirically established ameliorative benefits, various electronic devices (for example, Edinburgh Masker, portable fluency aids) have been developed to treat stuttering (Gruber, 1971;Dewar et al, 1979;Low and Lindsay, 1979;Stuart et al, 2003). However, these electronic devices need to be evaluated for their abilities to deliver 'effective' and 'efficient' treatment of stuttering and to be compared to other therapeutic modalities (for example, behavioral therapies) using similar criteria.…”
Section: Introductionmentioning
confidence: 97%